New Tools to Study Contact Activation - Rosén, Steffen (Frontiers in Medicine, 2016)
The recent availability of a sensitive chromogenic method approach for determination of FXIa activity has been explored for designing sensitive methods for FXIIa and Kallikrein, both using FXa formation as the read-out. For both enzymes the assay range 1-10 nmol/L provides a resolution of about 0.8 absorbance units with a total assay time of about 20 min. For studies on activation kinetics, subsampling and extensive dilution can be performed in MES-BSA buffer pH 5.7 for quenching of enzyme activity and with ensuing determination of FXa generation in a chromogenic FXIa method. Optionally, suitable inhibitors such as Aprotinin and/or CTI may be included. The stability of FXIa, FXIIa and Kallikrein in MES-BSA buffer was shown to be at least 5 hours on ice. In conclusion, the use of a sensitive chromogenic FXIa method either per se or in combination with MES-BSA buffer pH 5.7 are new and potentially valuable tools for study of contact factor enzymes and their inhibitors. So far, dose-response studies of FXIIa and Kallikrein have been limited to purified systems and hence more data are required to learn whether these new methods might or might not be applicable to determination of FXIIa and Kallikrein activities in plasma.